Evaluation of cover crops drill‐interseeded into corn across the Mid‐Atlantic. Issue 5 (4th October 2018) - Curran, W.S.; Hoover, R.J.; Roth, G.W.; Wallace, J.M.; Dempsey, M.A.; Mirsky, S.B.; Ackroyd, V.J.; Ryan, M.R.; Pelzer, C.J.
Abstract : This article reports on field experiments that addressed two primary objectives: (1) compare cover crop establishment and biomass production of drill‐interseeded grass and legume cover crops and corn performance across the Mid‐Atlantic region and (2) determine if timing of interseeding cover crops into corn (V2–V6) influences cover crop performance and corn grain yield. Earn 1.5 CEUs in Soil & Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/614 .